Self-help based on subjective experiences in connection with epileptic seizures - Johanson, Mirja (Rehabilitacija (Ljubljana), 2012)
Subjective experiences in connection with epileptic seizures are the core information about how it is to have a seizure. Such knowledge is important in patient education, selfcontrol of seizures and necessary for developing adequate therapeutic interventions that are based on patient perspective. Also, by studying subjective experiences, we can promote further research on the relationships between subjective experiences and "objective" measurements in order to gain a deeper understanding of the phenomenon of epilepsy.
Keywords: coping; epilepsija; Epilepsy; epileptic seizures; epileptični napadi; rehabilitacija; Rehabilitation; samonadzor; self-control; subjective experience; subjektivne izkušnje; vocational rehabilitation